2020
DOI: 10.1161/circresaha.120.317415
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Regulation of Atherosclerosis-Relevant Phenotypes in Human Vascular Smooth Muscle Cells

Abstract: Rationale: Coronary artery disease (CAD) is a major cause of morbidity and mortality worldwide. Recent genome-wide association studies (GWAS) revealed 163 loci associated with CAD. However, the precise molecular mechanisms by which the majority of these loci increase CAD risk are not known. Vascular smooth muscle cells (VSMCs) are critical in the development of CAD. They can play either beneficial or detrimental roles in lesion pathogenesis, depending on the nature of their phenotypic changes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
88
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(95 citation statements)
references
References 80 publications
(81 reference statements)
4
88
3
Order By: Relevance
“…In addition, a lower level of ZC3HC1 mRNA significantly enhanced the proliferation of SMCs at 72 h, but not at earlier time points. This finding was in agreement with the results from genotyped SMCs derived from 151 human donors 16 , in which no significant correlation was observed between the T allele and cell proliferation at 24 h. Transcriptional profiling of ZC3HC1 downregulation in human SMCs: To determine the transcriptional profile of ZC3HC1 downregulation, transcriptome analysis using RNA sequencing was performed in aortic SMCs in the presence or absence of 5 ng/mL PDGF-BB.…”
Section: Downregulation Of Zc3hc1 In Human Smc Increases Migration and Proliferationsupporting
confidence: 88%
See 3 more Smart Citations
“…In addition, a lower level of ZC3HC1 mRNA significantly enhanced the proliferation of SMCs at 72 h, but not at earlier time points. This finding was in agreement with the results from genotyped SMCs derived from 151 human donors 16 , in which no significant correlation was observed between the T allele and cell proliferation at 24 h. Transcriptional profiling of ZC3HC1 downregulation in human SMCs: To determine the transcriptional profile of ZC3HC1 downregulation, transcriptome analysis using RNA sequencing was performed in aortic SMCs in the presence or absence of 5 ng/mL PDGF-BB.…”
Section: Downregulation Of Zc3hc1 In Human Smc Increases Migration and Proliferationsupporting
confidence: 88%
“…Analysis of the publicly available GTEx dataset eQTL (V8) showed that the genetic variant rs11556924-T results in reduced ZC3HC1 gene expression in heart (atrial appendage and left ventricle) and skin samples. Because eQTL effects are often cell type specific, we tested whether an eQTL was present in aortic SMCs from 151 heart transplant donors 16 , finding that SMCs from donors carrying the rs11556924-T allele have lower ZC3HC1 expression and migrate faster than SMCs from donors carrying the rs11556924-C allele. The absence of a significant association between ZC3HC1 expression and rs11556924 in blood samples 9 , monocytes/macrophages 28 and aortic endothelial cells 29 suggests that the regulatory impact of the variant at the ZC3HC1 locus is specific to SMCs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cigarette smoking constitutes a major environmental risk factor for atherosclerosis. Gene-environment interactions have also been demonstrated [99,100]. Indeed, a synergistic effect between cigarette smoking and the carrier state of the ApoE epsilon4 allele increases the risk of atherosclerosis [101].…”
Section: Environment Factors In Atherosclerosismentioning
confidence: 99%